The Effect of Emotional Intelligence on Social Media Advertising Perception - Kılıçarslan, Menekşe (International Journal of Computational and Experimental Science and Engineering, 2024)
Changing technological conditions are reflected in our lifestyles and online shopping has become more common day by day. In this case, social media tools used sparingly have become a powerful marketing tool. The combination of advertising is the theory of communication and is done with the aim of making them take the purchasing action. The motivation that forms the beginning of purchasing is heavily influenced by emotions. The concept of emotional intelligence, which is becoming more important day by day, has achieved the success it deserves within the discipline. The purpose of this study is to measure whether emotional intelligence has an impact on marketing or prospective customers' perceptions of advertisements they have observed on social media. Depending on the situation of the study, it has been observed that emotional intelligence has a statistically significant effect on social media advertising perception.